A Pilot Study on Measuring the Readers’ Emotions Using HRV Biofeedback at University Malaysia Pahang - Iftikhar Yousaf, Muhammad; Muhammad Nubli, Abdul Wahab; Nor Ashikin, Abdul Aziz; Muhammad, Iqbal (Australian International Academic Centre PTY. LTD., 2016)
Positive associations have been found between reading and emotions. Various techniques, including traditional as well as modern, have been used to measure emotions in the previous studies. However, emotional measurement of the readers of a literary piece through HRV Biofeedback has never been investigated. A study was undertaken to assess whether Heart Rate Variability (HRV) biofeedback regarding measurement of emotions in the readers of English Literature is likely to be effective or not for the first time at University Malaysia Pahang. In this study two scripts of the plays “Dr. Faustus” and “Waiting for Godot” were used. The Scripts were prepared from the Original Texts of these two plays, which might convey the overall message of the plays to the readers and resultantly produce the desired effect on the readers’ emotions. The total words of these two scripts were around 1050 each, allowing the students to complete one script in 7-8 minutes. Six subjects were selected randomly. While they were sitting calm and quiet at the desk, photoplethysmograph sensor was attached to their one of the earlobes which was connected to the emWave Desktop-PC software to record their Baseline HRV. The subjects, one at a time, read the Script 1 “Waiting for Godot” silently. After completion of the reading of Script 1, the emWave software was stopped and the HRV of the subject was recorded and saved automatically in the computer. The same process was repeated with Script 2 “Dr. Faustus”. In this way, emWave software recorded three HRV data for every subject. Results show obvious changes and significant correlations in the HRV of the participants while reading both the scripts. VLF increased for Script 1 while it decreased for Script 2. On the other hand, HF increased for Script 1 and further increased for Script 2. LF decreased for Script 1 and increased for Script 2. These results point out the tendency that the stress level of the participants was increased while they read the Script1“Waiting for Godot”- which conveys the message that ‘there is no God’ and vice a versa. This further indicates that the literature reading affects the reader’s emotions which may be successfully measured using HRV Biofeedback.